2021
DOI: 10.1007/s44202-021-00003-5
|View full text |Cite
|
Sign up to set email alerts
|

Suicide ideation and psychosocial distress among refugee adolescents in Bidibidi settlement in West Nile, Uganda

Abstract: This study investigated the factors associated with suicidal ideation and psychological distress among Sudanese refugees (aged 10–19 years) in Bidibidi refugee settlement, Yumbe district, Uganda. The analysis is based on cross-sectional data collected as part of the implementation of a project on sexual and reproductive health in Bidibidi refugee settlement. Data were collected from 284 South Sudanese adolescents in July 2020. We estimated the prevalence of psychological distress and suicidal ideation, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…Another study conducted among adolescents living with HIV/AIDS in Uganda reported a comparable rate of 51% psychological distress [ 30 ]. Contrary to the present study findings, a study conducted among refugee adolescents in West Nile, Uganda reported a much lower prevalence of psychological distress (12.3%) [ 7 ]. The stress and pressure associated with secondary school education and high expectations from the teachers and parents or guardian of these students might explain the high prevalence of psychological distress among the school-going adolescents reported in the present study [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another study conducted among adolescents living with HIV/AIDS in Uganda reported a comparable rate of 51% psychological distress [ 30 ]. Contrary to the present study findings, a study conducted among refugee adolescents in West Nile, Uganda reported a much lower prevalence of psychological distress (12.3%) [ 7 ]. The stress and pressure associated with secondary school education and high expectations from the teachers and parents or guardian of these students might explain the high prevalence of psychological distress among the school-going adolescents reported in the present study [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Mental health conditions (including psychological distress) are a public health challenge that affects daily activities of adolescents including their school and work performance, relationships with family and friends, and involvement in the community [ 2 , 5 ]. Psychological distress has been associated with several negative consequences such as suicidal ideation and attempt [ 6 , 7 ], poor academic performance [ 8 ] and poor physical health [ 9 , 10 ] among adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of suicidal ideation was 6.3% in a sample of university students ( 10 ); another study found that the prevalence of suicidal ideation among adolescents was as high as 30.6% ( 11 ). Among the refugees hosted in Uganda, the prevalence of suicidal ideation is 5% ( 12 ). A range of factors are associated with suicidal ideation including financial difficulties ( 13 ), family breakdown or conflicts ( 14 ), and trauma ( 11 ), unemployment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%